Setting The Principles of Democracy in The Appointment of A Single Candidate Spouse of Regional Heads - Rahmat Nur (Jurnal Hukum Volkgeist, 2021)
This research aims to analyzethe regulation of democratic principles in filling the position of regional head in single candidatepai. This study uses normative juridical research by conducting legal analysis of legislation related to the filling of local government positions and legal issues related to the Decision of the Constitutional Court No. 100/PUU-XIII/2015 on the constitutional requirements of regional head elections (candidates' spouses). The results showed the regulation of democratic principles in filling the position of regional head in the case of a single candidate pair can use two mechanisms, namely using the electoral mechanism (Basedon Law No. 10 of 2016 as a follow-up to the Decision of Mk No. 100/PUU-XIII/2015) or the mechanism of appointment, as long as the appointment is done by officials who have been directly elected. Furthermore, the arrangement of the mechanism of appointing a single candidate of regional head in Indonesia can follow what has been implemented in the United States that implements uncontested elections if after the nomination period ends still produces only one candidate, then the candidate's spouse is immediately considered valid as the spouse of the elected candidate and can be legally appointed as the head of the new period. Filling the position of regional head that there is only 1 (one) candidate pair is using the mechanism of appointment, while if there are 2 (two) pairs of candidates or more still use the election mechanism.